Intractable chronic constipation in children: Outcome after anorectal myectomy - Seyed Abdollah Mousavi; Hasan Karami; Ahmad Ali Rajabpoor (Wolters Kluwer Medknow Publications, 2014)
Background: Many children with constipation fail to respond with conventional medical therapy. Surgery can produce a good result in dysfunction of the colon secondary to aganglionosis. However, its role in treating idiopathic constipation is more controversial. Patients and Methods: A consecutive series of 44 patients with chronic idiopathic intractable constipation were included in this study. All children were investigated by barium enema and anorectal manometry. Due to inadequate response to medical therapy, all of these patients were selected for internal sphincter myomectomy. Patients were followed-up from 3 to 12 months. Results: Short-term (3 months) and long-term (6 months) follow-up was available for all patients. The histology examinations showed normal ganglion cells in 32, hypoganglionosis in eight and aganglionosis in four patients. In short-term, regular bowel habits, without the need for laxatives or low dose drugs were recorded in 35 patients (79.5%). Overall there was an improvement in 68.2% of the children after 6 months follow-up. There was not any correlation between histopathological findings, duration of symptoms, age and sex of operation and response to myectomy. Conclusion: anorectal myectomy is an effective procedure in patients with intractable idiopathic constipation. It relieves symptoms in 68.2% of patients with chronic refractory constipation.